Imaging and spectroscopic analysis of living cells: live cell imaging of cellular elements and functions - Conn, Patrick Michael (Methods in enzymology, 2012)
This volume of Methods in Enzymology is the second of 3 parts looking at current methodology for the imaging and spectroscopic analysis of live cells. The chapters provide hints and tricks not available in primary research publications. It is an invaluable resource for academics, researchers and students alike. Expert authors who are leaders in the field Extensively referenced and useful figures and tables Provides hints and tricks to facilitate reproduction of methods
Includes bibliographical references and indexes. - Print version record
Keywords: Electronic books; Spektroskopie; Zelle; Bildgebendes Verfahren